2021
DOI: 10.1101/2021.02.26.433000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perineuronal net receptor PTPσ regulates retention of memories

Abstract: Perineuronal nets (PNNs) have an important physiological role in retention of learning by restricting cognitive flexibility. Their deposition peaks after developmental periods of intensive learning, usually in late childhood, and they help in long-term preservation of new acquired skills and information. Modulation of PNN function by various techniques enhances plasticity and regulates retention of memories, which may be beneficial when memory persistence entails negative symptoms such as post-traumatic stress… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…Perhaps through dampening autophagic flux (Tran et al 2020), CSPGs through protein tyrosine phosphatase receptor sigma (PTPRσ) binding promote initial adhesion and receptor recruitment necessary for synaptogenesis (Han et al 2016;Bomkamp et al 2019). It has recently been found that the PNN-PTPRσ complex exerts its inhibitory action on neuronal plasticity, at least in part, by restricting signaling of the neurotrophic receptor tyrosine kinase 2 (TRKB) (Lesnikova et al 2021).…”
Section: Cspgs Impede Regeneration/plasticitymentioning
confidence: 99%
“…Perhaps through dampening autophagic flux (Tran et al 2020), CSPGs through protein tyrosine phosphatase receptor sigma (PTPRσ) binding promote initial adhesion and receptor recruitment necessary for synaptogenesis (Han et al 2016;Bomkamp et al 2019). It has recently been found that the PNN-PTPRσ complex exerts its inhibitory action on neuronal plasticity, at least in part, by restricting signaling of the neurotrophic receptor tyrosine kinase 2 (TRKB) (Lesnikova et al 2021).…”
Section: Cspgs Impede Regeneration/plasticitymentioning
confidence: 99%
“…The TRAP analysis also points towards the regulation of PNN s as the target of fluoxetine action. We have previously shown that plasticity promoted by the reduction of PNN s by chondroitinase treatment is also dependent on the expression of TrkB in PV interneurons and that this effect is mediated by the inhibition of the PNN receptor, receptor-type tyrosine-protein phosphatase Sigma (PTPRS) [39]. In addition, fluoxetine was shown to disrupt the interaction between TrkB and PTPRS, functionally mimicking the effects of PNN disruption [39].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that plasticity promoted by the reduction of PNN s by chondroitinase treatment is also dependent on the expression of TrkB in PV interneurons and that this effect is mediated by the inhibition of the PNN receptor, receptor-type tyrosine-protein phosphatase Sigma (PTPRS) [39]. In addition, fluoxetine was shown to disrupt the interaction between TrkB and PTPRS, functionally mimicking the effects of PNN disruption [39]. Furthermore, it appears that fluoxetine specifically targets PV + interneurons which was also observed in visual cortex plasticity [16].…”
Section: Discussionmentioning
confidence: 99%